Collaborative Governance in the Permitted Literacy Village Program, Jabon District, Sidoarjo Regency - Bayu Agung Arishandy; Hendra Sukmana (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
Online Single Submission (OSS) enables business stakeholders to develop a simpler and more efficient licensing mechanism. Online Single Submission is applicable in all Indonesian areas. Through Single Submission (OSS), the Business Identification Number (NIB) will be obtained, identifying the perpetrator business while conducting business. At the start of the COVID-19 pandemic, the population of the Jabon Subdistrict was unaware of the significance of obtaining business licenses for economic actors. The study aimed to identify the characteristics which enable the collaborative governance implementation in the permit literacy village program in the Jabon subdistrict of the Sidoarjo district. There was relatively little information on business licenses, benefits, procedures, tariff charges, and how to supply business licensing services in the community. The research approach was qualitative and descriptive. The researcher obtains their data from both primary and secondary sources. Data-gathering techniques get accurate field data through observations, interviews, and documentation. The conclusion was that the Permitted Literacy Village Program Collaborative Governance Process in Jabon District, Sidoarjo Regency